Bismuth-coated 80S15C bioactive glass scaffolds for photothermal antitumor therapy and bone regeneration - Du, Jianhang; Ding, Huifeng; Fu, Shengyang; Li, Dejian; Yu, Bin (Frontiers in Bioengineering and Biotechnology, 2023)
Malignant bone tumors usually occur in young people and have a high mortality and disability rate. Surgical excision commonly results in residual bone tumor cells and large bone defects, and conventional radiotherapy and chemotherapy may cause significant side effects. In this study, a bifunctional Bi-BG scaffold for near-infrared (NIR)-activated photothermal ablation of bone tumors and enhanced bone defect regeneration is fabricated by in-situ generation of NIR-absorbing Bi coating on the surface of a 3D-printing bioactive glass (BG) scaffold. The results show that Bi-BG scaffolds have outstanding photothermal performance. Bi-BG scaffolds not only significantly facilitate tumor cell ablation in vitro, but also effectively inhibit the growth of bone tumors in vivo. Furthermore, they exhibit excellent capability in promoting osteogenic differentiation and finally enhance new bone formation in the calvarial defects. These results successfully demonstrate that the Bi-BG scaffolds have bifunctional properties of photothermal antitumor therapy and bone regeneration, which offers an effective method to ablate malignant bone tumors based on photothermal effect.